Understanding China's political will for sustainability and conservation gains. Issue 1 (19th January 2023) - Cheung, Hubert; Feng, Yutong Phoenix; Hinsley, Amy; Lee, Tien Ming; Possingham, Hugh P.; Smith, Stephen N.; Thomas‐Walters, Laura; Wang, Yifu; Biggs, Duan
Abstract: Political will is a critical determinant of the success or failure of environmental policies and interventions. Harnessing the political will necessary to implement environmental solutions can be challenging because environmental priorities may compete with other societal interests in policymaking. Environmental solutions are more politically feasible if fundamentally aligned with the core interests of key policymakers. Understanding the political agendas of decision‐makers enables conservationists to identify where political will already exists, and allows environmental objectives to piggyback on the motivation to deliver results. In this paper, we explore the core interests of the Chinese leadership to uncover opportunities to leverage Beijing's political will for sustainability and conservation gains. China's growing influence on ecosystems and natural resource use both within and beyond its borders makes an analysis of its leadership's political will valuable and timely. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. 簡介: 政治意願是影響和執行環境政策時成與敗的關鍵因素。取得執行環保政策所需的政治意願是困難的，因為環境利益在決策過程中與其他社會利益相競爭。 倘若環保方案能配合關鍵政策制定者的核心利益，成功執行的可能性會更高。了解決策者的政治意向讓環保政策可協調依附而推動產生結果。 在本文中，我們探究了中國領導層的核心政治利益，借助北京已有的政治意願促進「保護環境」和可持續發展成果的機會。中國對境內外生態系統和天然資源使用的影響逐漸擴大，因此對其領導層的政治意願進行分析變得有價值和迫切。 简介: 政治意愿是影响和执行环境政策时成与败的关键因素。取得执行环保政策所需的政治意愿是困难的，因为环境利益在决策过程中与其他社会利益相竞争。 倘若环保方案能配合关键政策制定者的核心利益，成功执行的可能性会更高。了解决策者的政治意向让环保政策可协调依附而推动产生结果。 在本文中，我们探究了中国领导层的核心政治利益，借助北京已有的政治意愿促进「保护环境」和可持续发展成果的机会。中国对境内外生态系统和天然资源使用的影响逐渐扩大，因此对其领导层的政治意愿进行分析变得有价值和迫切。